CSR Disclosure Quality and Quantity: Do Corporate Governance and Multinationality Matters? - Rosaline Jeanette; Rizky Eriandani (Universitas Hayam Wuruk Perbanas, 2021)
This research aims to explain the effect of corporate governance and the degree of multinational activities on CSR disclosure quality and quantity in a multinational enterprises. This research uses samples of 97 multinational enterprises listed in Indonesia Stock Exchange within 2018-2020. CSR disclosure is measured by conducting a content analysis and they were analyzed using a multiple linear regression model. The results indicate that corporate governance variables that significantly affect CSR disclosure quality are independent commissioners and CSR committees. Independent commissioner harms CSR disclosure quality, while CSR committee has a positive effect on CSR disclosure quality. The results also show that corporate governance variables that significantly affect CSR disclosure quantity are Board size and CSR committee. Board size and CSR committee have a positive effect on CSR disclosure quantity. The degree of multinational activity does not affect CSR disclosure. This research contributes to the development of literature on CSR disclosure of multinational companies in developing countries. For multinational companies, this research can provide information on the importance of the characteristics of corporate governance, namely the size of the board of commissioners and CSR committees, in increasing CSR disclosure.